Effects of marginal vegetation removal on Odonata communities - Carvalho,Fernando Geraldo de (2013)
AIM: Here we assess the effects of habitat degradation on individuals of the two suborders of Odonata community of Borecaia river sub-basin. More specifically, we tested the hypothesis that Anisoptera richness would be positively affected by removal of vegetation; on the other hand, Zygoptera richness would be adversely affected by virtue of their ecophysiological requirements; METHODS: We selected 10 streams of similar orders, six preserved and four degraded. Streams characterized as preserved had values of Index of Habitat Integrity (HII) above 0.70 (0.77 ± 0.07, mean ± SD) and continuous forest on both sides with a minimum width of 70 meters. Each site was sampled three times on different days. The effect of vegetation removal on richness was assessed using richness estimated by first order Jackknife; RESULTS: Decreased physical integrity (measured with IIH) of streams had no significant effect on the estimated richness to Odonata in general. However, the estimated richness of Anisoptera showed an inverse relationship with the integrity (r² = 0.485, P = 0.025), i.e., there was a reduction in their species richness with increasing integrity; DISCUSSION: As a general pattern, Anisoptera presents higher richness in an altered site; on the other hand, Zygoptera presents higher richness in a preserved one. This pattern suggests that Odonata needs to be considered at the sub-order level to access the effects of habitat degradation on these insects. Because of its restrictions ecophysiological Odonata varied widely in their composition and species richness between the two types of environments, it reinforces the potential of the order of studies and environmental monitoring also shows that Zygoptera be more affected by changes in habitat. However, further studies including more samples and different streams are need to confirm this pattern, being an interesting line of research for future works.